Green Accounting Corporate Governance and Financial Performance: Akuntansi Hijau, Tata Kelola Perusahaan, dan Kinerja Keuangan - Tisa Norani Dewi; Duwi Rahayu (Indonesian Journal of Law and Economics Review, 2025)
General Background Corporate sustainability has become a central issue in assessing company performance amid growing environmental and governance demands. Specific Background The implementation of green accounting and good corporate governance is increasingly emphasized as part of corporate accountability and financial evaluation. Knowledge Gap Previous studies show inconsistent findings regarding the integration of environmental accounting practices, governance mechanisms, and financial outcomes, particularly in industrial sectors. Aims This study aims to examine the relationship between green accounting, corporate governance, and financial performance using empirical evidence from listed companies. Results The findings indicate that the examined variables demonstrate measurable associations with financial performance as reflected in the analyzed indicators. Novelty This research provides a comprehensive empirical model by simultaneously incorporating green accounting practices and governance structures within a single analytical framework. Implications The results offer insights for corporate management and stakeholders in aligning environmental responsibility and governance practices with financial evaluation processes. Keywords: Green Accounting, Corporate Governance, Financial Performance, Sustainability Reporting, Environmental Accounting Key Findings Highlights: Green accounting practices are empirically associated with financial performance indicators. Corporate governance mechanisms contribute to variations in company financial outcomes. Integrated environmental and governance analysis provides a broader assessment framework.